Sosialisasi Tindak Pidana Penyebaran Berita Bohong (Hoax) Pada Masyarakat di Kelurahan Limbungan - Yusuf Daeng; Tri Novita Sari Manihuruk; Olivia Anggi Johar (COMSEP: Jurnal Pengabdian Kepada Masyarakat, 2021)
A common problem faced by partners is that they do not understand the Crime of Spreading Hoax Based on Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Electronic Information and Transactions. They do not yet understand in detail what sanctions are given to spreaders of fake news (hoax) based on the ITE Law. The method of implementing activities is legal counseling. The delivery of material is carried out by lecturers who are members of the team that propose community service activities. In addition, this activity needs to involve the local Village Head as the activity facilitator. The result of this community service activity is an increase in public understanding of the Crime of Hoax Spreading Based on Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Electronic Information and Transactions